The curriculum conception in Dermeval Saviani and its relations with the marxist category of freedom - Gama, Carolina Nozella; Duarte, Newton [UNESP] (Univ Estadual Paulista-unesp, 2017)
Dermeval Saviani analyzes the educational work using the marxist approach, articulating issues relating to philosophy and history of education, educational policy and educational theory, providing inputs for coping with the emptying process suffered by the the school curriculum. From the contribution of Saviani and others regarding the construction of the historical-critical pedagogy, some curricular principles for the theachig content selection can be formulated. As an example, the question of the classics is pointed out by Saviani as a reference for the selection of school subjects. The category of freedom is understood following the marxist tradition in a way opposed to the liberal-bourgeois point of view based on the historical analysis of the construction of sociability and culture using work as foundation. This historical perspective gives meaning to the ideas proposed by Saviani regarding knowledge, human education and school curriculum.
Keywords: Curriculum; Dermeval Saviani; Historical-critical pedagogy; Freedom; Marxism